The potential dangers of whooping cough: a case of rib fracture and pneumothorax - Zatovkaňuková, Petra; Slíva, Jiří (BMC infectious diseases, 2024)
BACKGROUND: Pertussis, also known as whooping cough, is an acute respiratory illness primarily caused by Bordetella pertussis. Highly contagious, it poses significant morbidity and mortality risks, especially in infants. Despite widespread vaccination efforts, pertussis cases have recently resurged globally. This case report details possible complication in a 48-year-old woman, involving a cough-induced rib fracture and recurrent pneumothorax, highlighting the need for considering pertussis in patients with severe cough and back pain. CASE PRESENTATION: A 48-year-old female non-smoker with hypertension, treated with ACE inhibitor (perindopril), presented with a runny nose, productive cough, and back pain. Initial treatment for a common cold provided temporary relief. However, her symptoms worsened, and further examination revealed a fractured rib, pneumothorax, and subcutaneous emphysema. Laboratory tests confirmed elevated Bordetella pertussis toxin antibodies. She was treated with antibiotics, and despite recurrent symptoms, a conservative management approach was successful. Follow-up indicated resolution of symptoms, but significant anxiety related to her condition. CONCLUSION: This case emphasises the importance of considering pertussis in adults, as early symptoms resembling a common cold can lead to misdiagnosis. It also highlights the potential for significant musculoskeletal and pulmonary injuries due to intense coughing associated with pertussis. Prompt diagnosis and comprehensive management, including antibiotics and supportive care, are essential for favorable outcomes.
Keywords: Back pain; fraktury žeber; Pneumothorax; pneumotorax; Whooping Cough; lidé středního věku; Pertussis; lidé; pertuse; Middle Aged; kašel; Female; Anti-Bacterial Agents; Rib fracture; Rib Fractures; ženské pohlaví; Humans; Bordetella pertussis; antibakteriální látky; Cough